Using a mixed international comparable methodological approach in a European Commission project on gender and engineering - Sagebiel, Felizitas,Hoffmeyer-Zlotnik, Jürgen H. P.,Harkness, Janet (online, 2005)
Abstract: Gegenstand des Beitrags ist das europäische Forschungsprojekt
urn:nbn:de:0168-ssoar-49146-2
Keywords: (thesoz)qualitative Methode; (thesoz)quantitative Methode; (thesoz)Forschungsprojekt; (thesoz)Geschlechterforschung; (thesoz)Berufsforschung; (thesoz)internationaler Vergleich; (thesoz)Fragebogen; (thesoz)Stichprobe; (thesoz)Validität; (thesoz)Reliabilität; (thesoz)Befragung; (thesoz)Beobachtung; (thesoz)interkultureller Vergleich; (thesoz)EU-Staat; (thesoz)Ingenieur